Metastatic follicular thyroid carcinoma to the mandible: a case report - Zain, R.B.; Ismail, S.B.; Abraham, M.T.; Zaini, Z.B.; Yaacob, H.B. (Elsevier, 2009)
Introduction: Metastatic lesions to the oro-facial region may be the first evidence of dissemination of an unknown tumour from its primary site. Case presentation: We described a case of metastatic follicular thyroid carcinoma to the mandible presenting with pain and loosening of teeth in a 70 years old female patient leading to extraction of the loose teeth. Conclusion: The present case emphasizes the importance of considering metastasis in the differential diagnosis of swelling related to loosening of teeth, even though the patient had no history of any malignant disease. © 2009 Ismail et al; licensee Cases Network Ltd.